PERANCANGAN LAYANAN INTERNET RADIO UNTUK RADIO KONVENSIONAL (Studi Kasus Radio Konvensional di Kota Bandung) - Sindu Prawito, Ponsen; Fachrurrizal, Afdan (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
The design of internet radio services for conventional radio, especially in the city of Bandung was made, because at this time many new services have sprung up with various innovations that can create new markets and can also "disrupt" or damage existing markets. This happens in various industries, including the conventional radio industry. The presence of new services such as internet radio, audio streaming, or music streaming can disrupt the services provided by conventional radio, especially in the city of Bandung. This can reduce customers and conventional radio revenue. Radio internet services can be a radio solution to stay afloat. Therefore, the radio industry needs a radio internet service plan that can describe internet radio services ranging from business to information technology. This study aims to make the design of internet radio services that are expected to be a solution to increase the potential for conventional radio revenue. Internet Radio is designed not only as a live broadcast service as it is today, but must be able to provide services that remain in accordance with the expertise of the radio industry and also with additional capabilities that are more in line with customer needs today.